(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article considers the goals of developing the field of natural science in primary education. It studies current literature, analyzes existing methods, provides potential results, participates in a discussion on defined trends, and concludes with proposals for creating a more robust and effective curriculum for natural sciences in primary schools.